Quantifying Semantics Using Statistical Tools: An Empirical Research in Colour Compounds in Modern Greek - Serakioti, Dimitra (European Scientific Journal, ESJ, 2020)
The present paper attempts an empirical investigation of the semantic impact of colour compounds in Modern Greek interpretation. The study adopted the framework put forward by Berlin and Kay (1969), statistical tools were used for data analysis and Venn diagrams depicted the relationship between the compounding elements. Taking into consideration that the research literature supports the view that colour compounds may be considered as coordinates, and despite the intuition, that native speakers are likely to consider the second constituent as basic one according to the Righthand Head Rule that applies for Greek, the results of our experiments negate our two hypotheses. Specifically, respondents’ perception regarding colour compounds tends to acknowledge the first constituent as strongest. This might well be attributed to the gradual left-to-right speech processing, as observed at the sentence level. Moreover, the alternate order of the constituents does not lead to different intuitions.